Muraqabah dalam Perspektif Tarekat Naqsyabandiyah Al-Khalidiyah Al-Kurdiyah - Faisal Muhammad Nur (Program Studi Aqidah dan Filsafat Islam, 2021)
This article describes the concept of muraqabah as a method to get closer to Allah SWT. This method is implemented by every follower of the sect of al-naqsyabandiyah al-mujaddidiyah al-khalidiyah al-kurdiyah at all times. the data in this study were collected through a literature review. This study concludes that the concept of muraqabah will create awareness in performing worship to God. However, in this concept, the results obtained depend on a person's personality in performing dhikr and the feeling that they are always under the supervision of Allah SWT. Therefore, the level obtained will differ from one person to another based on their experience and their meaning of dhikr in their daily lives